Pengaruh Komunikasi dan Lingkungan Kerja Terhadap Kinerja Pegawai CV. Santoso Teknik Karawang - Adelia Pritasari Kusumawardani; Aji Tuhagana; Zenita Apriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out how employees perform at CV. Santoso Teknik Karawang is influenced by communication and the work environment. Descriptive and verification methods using a quantitative approach are the research methodology used. The population of this study was 50 employees or all CV employees. Santoso Engineering Karawang. Non-probability sampling techniques are applied in the sampling process because each member is sampled. A Likert scale questionnaire was used as part of the data collection method. Validity test, reliability test, classical assumption test, multiple linear regression test, t test, f test, and determinant coefficients are some of the data analysis techniques used and processed with the SPSS version 22 application. The findings from the t-test show that communication has a partially significant effect on employee performance, while the work environment does not have a significant effect on employee performance. The f-test of this research shows communication and work environment at CV. Santoso Teknik Karawang simultaneously has a significant effect on the performance of CV employees. Santoso Engineering Karawang.